A “Rasura Escrita” em poemas inventados por alunos de 2º e 3º ano do Ensino fundamental: análise de suas ocorrências - Cavalcante, Frazio Valdez Tenório (2010)
This research analyzes the occurrence of “written erasures” present in the final product of three poems invented by couples of 2nd and 3rd grade children of a philanthropic school situated in a Maceió suburb. It emerges from the need to investigate what is behind the erasure, its backstage and its propulsory forces, by understanding it not as an end in itself, but as the means to investigate the comes and goes of the scriptor and the engagement between him and the language. The process of scripture in act is analyzed after the transcription by the annotator/researcher of the children´s production footage, for which the resources of the program ELAN (Eudico Linguistic Annotator) are used, a software holder of professional tools for the creation of complex annotations of audio and video resources. Even though the main object are the “written erasures”, understood as those that leave marks on the paper sheet, the analysis made is not restricted to the final product of this textual practices, in fact, it considers all the context in which the erasure was produced. Therefore, it all starts with the perspective in which it is indispensable to observe and analyze the process of scripture in act, so that the circumstances and even the reason why certain erasure was made can be understood. The praising of the process, in detriment of a study focused only in the final product, reveals important aspects of the relation between subject and language. Having the “written erasure” as a starting point and by studying it under the light of the scripture in act process, it realizes that the error is not indispensable for the existence of an erasure, neither ignorance is a determiner factor for error. Through this methodology it is possible to identify moments in which the language operates over the scriptor, whether it frozens him in pre-established structures, conducting him to unexpected directions and, for times, undesired, when not it simply deserts him or keeps him from going on, moments exteriorized by silence that, many times, precedes the act of making the erasure.